2001
DOI: 10.1103/physrevd.63.053013
|View full text |Cite
|
Sign up to set email alerts
|

Top quark production at future lepton colliders in the asymptotic regime

Abstract: The production of a tt(bar) pair from lepton-antilepton annihilation is considered for values of the center of mass energy much larger than the top mass, typically of the few TeV size. In this regime a number of simplifications occurs that allows to derive the leading asymptotic terms of various observables using the same theoretical description that was used for light quark production. Explicit examples are shown for the Standard Model and the Minimal Supersymmetric Standard Model cases.Comment: 20 pages and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 21 publications
5
86
0
Order By: Relevance
“…[9,11], because of a typical gauge cancellation between splitting and parameter renormalization, the contributions to the single log cancels, and it remains only the quadratic log contribution feeded by the three gauge boson coupling, which is a pure SM term. So, owing to this cancellation, the universal coefficient is the same in all cases (SM, Split, "m.l.…”
Section: A) External Leptons and Quarks Pairsmentioning
confidence: 99%
See 3 more Smart Citations
“…[9,11], because of a typical gauge cancellation between splitting and parameter renormalization, the contributions to the single log cancels, and it remains only the quadratic log contribution feeded by the three gauge boson coupling, which is a pure SM term. So, owing to this cancellation, the universal coefficient is the same in all cases (SM, Split, "m.l.…”
Section: A) External Leptons and Quarks Pairsmentioning
confidence: 99%
“…For what concerns the notations and the conventions, we shall follow the same ones as in Ref. [7][8][9]. To make, though, this Section more easily and quickly readable by a reader who were not too interested in the technical details, we have devoted a final Appendix to the complete definition of the several terms that appear in our formulae.…”
Section: Electroweak Sudakov Expansions For Split Supersymmetrymentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the invariant amplitudes defined in (A.4), they are written as 9) and for all processes it is found that N Born, t 3,9 = N Born, u…”
Section: Observablesmentioning
confidence: 99%